Molecular epidemiology of Campylobacter jejuni isolates from the broiler production chain: first report of MLST profiles in Argentina = Epidemiología molecular de Campylobacter jejuni aislados de la cadena cárnica aviar: primer reporte de perfiles de MLST en Argentina - Zbrun, María Virginia; Rossler, Eugenia; Soto, Lorena Paola; Rosmini, Marcelo Raúl; Sequeira, Gabriel Jorge; Frizzo, Laureano Sebastian; Signorini Porchiett, Marcelo Lisandro (Elsevier, 2021)
Campylobacter jejuni is an important foodborne pathogen with global distribution. We describe a genotyping study of a collection of C. jejuni (n = 137) isolated from different broiler farms and from multiple sites along the processing line in a slaughterhouse in Argentina during 2011, 2012 and 2015. The isolates were genotyped using pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Based on the PFGE results, the isolates were grouped into 26 pulsotypes. Subsequently, the isolates representing these 26 pulsotypes were chosen for MLST genotyping, which identified 16 different sequence types (STs) and 6 clonal complexes (CCs) (21, 45, 48, 353, 354, 446). Several of the STs (n = 7) have not been previously reported in the PubMLST.org database. The most prevalent CCs were 21, 45 (both associated with human campylobacteriosis worldwide) and 353. This study showed high genetic diversity among C. jejuni in the broiler production environment in Argentina with novel MLST genotypes.